Carbon Reservoir Effects in Eastern Oyster from Apalachicola Bay, USA. Issue 5 (12th May 2017) - Hadden, Carla S; Cherkinsky, Alexander
Abstract: Eastern oyster ( Crassostrea virginica ) is an ubiquitous estuarine shellfish taxon in eastern North America and one of the most abundant materials available for radiocarbon ( 14 C) dating. We examine spatiotemporal variability in carbon reservoir effects among pre-bomb oysters from Apalachicola Bay, USA, a river-influenced estuary on the northern Gulf of Mexico. Shells were sampled at multiple points along the valve to produce time-series records of 14 C variation during the lives of the mollusks. Conventional ages within shells differed by as little as 36 14 C yr to as much as 295 14 C yr. Reservoir offsets varied sub-regionally within the estuary, increasing from 92±37 yr in the eastern edge of study region to 227±110 yr in the west, reflecting the influence of 14 C-depleted dissolved inorganic carbon from the Apalachicola River. Dynamic carbon reservoirs can pose problems for the estimation of ΔR and for building coastal chronologies. Estimating sub-regional ΔR values can be useful for assessing the range of variability in reservoir offsets within an estuary, and for correcting sample ages if the shell origin is known. Greater variability and/or uncertainty in ΔR lead to greater uncertainty in the calibrated age.